ÍNDICE DE MEMBRANAS DEGRADADAS COMO UM TESTE DE VIGOR EM SEMENTES DE ALGODÃO - SILVA, Kelly Gabriela Pereira da; OLIVEIRA, Izadora Araujo; FERREIRA, João Pedro de Souza Barbosa; BRAMBILLA, Henry Vinicius Ribeiro; SILVA, Ricardo Leonel; ZOZ, Tiago (ANAIS DO ENIC, 2022)
-